Effects of Gender Equality Regulations in the Presence ofWomen in Spanish Hybrid Entities - Acerete, Basilio; Gasca, Mar; Yetano, Ana (Revista del CLAD Reforma y Democracia, 2022)
Talent is not, nor should it be, a gender issue. However, the underrepresentation of women in the governing bodies of organisations is a fact. Spanish regulations have legislated to promote equality between the sexes in the workplace, introducing the principle of balanced presence of women and men on the boards of directors of trading companies. This paper is not based on the hypothesis that the integration of the women generates improvements in the management or the performance of an entity. The objective is to analyse to which extent does the dissemination of information on gender reflects the evolution of the presence of women at different organizational levels of hybrid entities, as a result of regulations issued by the public authorities. Compared to studies focused on the public or private sectors, hybrid entities have a duality in their configuration: their mission is typical of a public entity, providing a public service, which is developed through a private business structure. The sample consists of twenty-four Spanish toll road concessionaires during the period 2007-2018, divided into two groups according to weather they started their activity in the 20th century or only developed it in the 21st century. The results show a heterogeneous situation within the sector and that the mere suggestion of quotas does not seem effective to meet the equality objectives set. Although the presence of women in the case of the most recent concessionaires has improved, because the sociocultural context in which they are born affects their behaviour in this field, there is a perceived lack of a clear strategy that would allow them to participate on equal terms in the different levels of the company. There is also a lack of career policies that considers gender as a variable to bear in mind. The disclosure of information in the financial statement serves to highlight the reality so that public managers can design suitable policies that include reinforcement measures.